Pengaruh Insentif dan Disiplin terhadap Motivasi Serta Dampaknya terhadap Kinerja Pegawai di Satuan Polisi Pamong Praja Kota Jambi - Ratna Sari (Universitas Batanghari Jambi, 2022)
This study aims to determine whether there is a significant effect between variables X1 (incentives), X2 (discipline) on Y (motivation) and the impact on Z (performance) of employees at the Jambi City Civil Service Police Unit. The object of research in this study is all non-permanent employees (PTT) and civil servant staff (PNS) totaling 143 people, with data sources obtained from direct respondent questionnaires as well as literature studies and other external data. This study uses quantitative descriptive analysis and the data is processed using SPSS 22 with a path analysis approach. The results showed that the total effect of X1 and X2 on Y was 40.69%. The total effect of X1 and X2 on Z is 35.34%. From the comparison results, it can be seen that t-count is greater than t-table (t-count > t-table). Thus Ho is rejected and Ha is accepted. By comparing the number of significant levels (sig) of research with a significant level of 0.05 then 0.000 <0.05, it can be said that there is a significant influence between the Incentive (X1) and Discipline (X2) variables on Motivation (Y) and their impact on Performance (Z) an employee at the Jambi City Civil Service Police Unit.